2018
DOI: 10.1002/nafm.10042
|View full text |Cite
|
Sign up to set email alerts
|

Population‐Specific Migration Patterns of Wild Adult Summer‐Run Chinook Salmon Passing Wells Dam, Washington

Abstract: Summer‐run Chinook Salmon Oncorhynchus tshawytscha migrating over Wells Dam, Washington, enter a habitat characterized by blocked upstream access, high tributary water temperature regimes, and robust tribal and recreational fisheries. In 2011, we initiated a 2‐year radiotelemetry study to identify population‐specific run timing, movement, and mortality of naturally produced fish passing the dam. Five hundred seventeen salmon were radio‐tagged at Wells Dam over 2 years of study. The highest proportion (44%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…We released 255 radio‐tagged fish in 2011 and 262 radio‐tagged fish in 2012, representing 1.8% and 1.6%, respectively, of the wild summer‐run Chinook Salmon passing Wells Dam in those years. Through the subsequent radio‐tracking effort, we estimated parameters that affected postrelease distribution and escapement estimation, including tag loss, dam fallback, harvest, and prespawn mortality (see Mann and Snow ). However, most fish that were tracked upstream of Wells Dam were spatially and temporally located to suggest survival to spawning (52% of tagged fish), including a small population of Columbia River main‐stem‐spawning fish (4.8% of tagged fish).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We released 255 radio‐tagged fish in 2011 and 262 radio‐tagged fish in 2012, representing 1.8% and 1.6%, respectively, of the wild summer‐run Chinook Salmon passing Wells Dam in those years. Through the subsequent radio‐tracking effort, we estimated parameters that affected postrelease distribution and escapement estimation, including tag loss, dam fallback, harvest, and prespawn mortality (see Mann and Snow ). However, most fish that were tracked upstream of Wells Dam were spatially and temporally located to suggest survival to spawning (52% of tagged fish), including a small population of Columbia River main‐stem‐spawning fish (4.8% of tagged fish).…”
Section: Resultsmentioning
confidence: 99%
“…We radio‐tagged and released 517 wild summer‐run Chinook Salmon over 2 years (2011 and 2012) as part of a study to describe stock‐specific migration timing over Wells Dam (Mann and Snow ). These fish were collected between late June and late October of each year by operating adult salmonid trapping facilities at the west‐bank and east‐bank fish passage ladders at Wells Dam.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At WEL, the last passable dam on the Upper Columbia, the spring run is considerably lagged relative to BON due to travel times and the fall run is nearly non-existent in some years ( Fig 2i ). At this dam, it has previously been found that fallback and re-ascension at the fish passage causes more overestimates in salmon counts relative to lower elevation dams [ 40 ]. While we do not explicitly account for this source of error, it illustrates how uncertainties can vary between dams.…”
Section: Methods: Characterizing Dependencies In the Crb Systemmentioning
confidence: 99%